Clinical and Laboratory Parameters of Metabolic Syndrome in Chronic Spontaneous Urticaria: A Cross-Sectional Study - M. Thanoj K. Reddy; Seetharam A. Kolalapudi; Seva Praveen; Subhashini Konala; Gunnam L. Rasajna; Saloni S. Khutate (Indian Dermatology Online Journal)
Background: Chronic spontaneous urticaria (CSU) appears to share some pathomechanisms with metabolic syndrome (MS), such as proinflammatory state, increased oxidative stress, changes in adipokine profile, and coagulation system activation. Aim and Objectives: To evaluate clinical and laboratory parameters of MS in CSU patients and to assess relationship of MS with duration and severity of CSU, Ig-E, thyroid-stimulating hormone (TSH), C-reactive protein (CRP), and autologous serum skin test (ASST). Materials and Methods: A hospital-based cross-sectional study was conducted on 131 CSU cases and 131 controls who were age- and sex-matched. Duration of the CSU and urticaria activity score (UAS) were noted. Waist circumference (WC), blood pressure, fasting blood sugar, high-density lipoprotein (HDL), triglycerides (TG), CRP, TSH, IgE, and ASST were noted. MS was considered according to Harmonization Asian criteria. Results: The percentage of patients with elevated clinical and laboratory parameters of MS was higher in cases compared to controls, in which WC, HDL, and TG were significantly elevated. MS was positive in 25.19% and 14.50% of cases and controls, respectively (P = 0.044). Cases with MS had a significant higher mean duration (16.60 months) than those without MS (8.81 months) (P = 0.004). MS was positive in 15.2%, 32.3%, and 36.4% of mild, moderate, and severe UAS patients, respectively (P = 0.095). Patients with increased TSH and CRP had a significantly higher percentage of MS (68.4% and 40.7%, respectively) than with normal TSH and CRP (15% and 19.4%, respectively) (P < 0.05), while it was not significant with respect to IgE and ASST. Limitations: Small sample size and it was a hospital-based study, therefore, all controls were from the patients attending our outpatient department only and could not be compared with the general population. Conclusion: MS is not uncommon in CSU patients. The duration of CSU, CRP levels, and TSH levels have a significant positive correlation with MS. Screening, along with regular surveillance of CSU patients, aids in the early detection of MS and minimizes the risk of cardiovascular disease.